Penerapan SDKI, SLKI, dan SIKI dalam Pendokumentasian Asuhan Keperawatan di Ruangan Interne Pria RSUP Dr. M. Djamil Padang - Yuanita Ananda; Yulastri Arif; Zifriyanthi Minanda Putri; Esthika Ariany Maisa; Dewi Murni; Sidaria Sidaria; Ilfa Khairina; Muthmainnah Muthmainnah; Susmiati Susmiati; Nelwati Nelwati (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2022)
Nursing services are often used as a benchmark for the image and quality of a hospital in the eyes of the public. One indicator of service quality is nursing documentation. Nursing documentation is a nursing care process for patients that must be carried out by nurses. The results of interviews conducted with nurses in the Men's Internal Room at RSUP Dr. M. Djamil Padang found that nursing documentation through IDHS, SLKI, and SIKI had not run optimally. Therefore, it is necessary to provide education on the application of the SDKI, SLKI, and SIKI in carrying out nursing documentation. The purpose of this activity is that nurses can apply nursing documentation with SDKI, SLKI, SIKI to patients. The implementation of the activity was carried out directly to the nurses with a total of 30 respondents starting with the pretest, giving material, and ending with the post test. The results of the pre test were the level of knowledge of nurses in the Men's Internal Room of Dr. M. Djamil Hospital Padang regarding the application of SDKI, SLKI, and SIKI in nursing documentation before being given education, namely 7 nurses had good knowledge (23%), 10 nurses had sufficient knowledge (33%), 13 nurses have less knowledge (44%). The results of the post test were the level of knowledge of nurses in the Men's Internal Room Dr. M. Djamil Hospital Padang regarding the application of SDKI, SLKI, and SIKI in nursing documentation after being given education, namely 25 nurses had good knowledge (83%), 5 nurses had sufficient knowledge (17%). Based on these results it can be concluded that this educational activity is very useful and can increase nurses' knowledge about documentation and can be applied directly to patients. The suggestion is that nursing managers can control the nursing documentation process so that the quality of nursing services can be optimal.